The historical Christ and the Jesus of faith : the incarnational narrative as history - Evans, C. Stephen (Oxford, Clarendon Press, 1996)
The New Testament contains a story about Jesus of Nazareth which has always been understood by the Church to be historically true. It is an account of the life, death, and resurrection of a real person, whose links with history are firmly signalled in the creeds of the early church. Contemporary historical scholarship, on the other hand, has called into question the reliability of the church's version of this story, and thereby raised the question as to whether ordinary people can know its historical truth. In this book, a leading philosopher of religion argues that the historicity of the story still matters, and that its religious significance cannot be captured by the category of "non-historical myth." The commonly drawn distinction between the Christ of faith and the Jesus of history cannot be maintained. The Christ who is the object of faith must be seen as historical; the Jesus who is reconstructed by historical scholarship is always shaped by commitments to faith. Evans looks carefully at contemporary New Testament studies, and the philosophical and literary assumptions upon which it rests, to show that this scholarship does not undermine the confidence of lay people who believe that they can know that the church's story about Jesus is true. His accessible and controversial study will interest all thoughtful Christian readers. -- Publisher description.
The incarnational narrative and the problem of its historicity --- Modernity's responses to the problem --- Why the events matter: history, meaning, and myth --- Why the events matter: God's atoning work --- Awareness of the narrative: do we need to know? --- Is the Incarnation logically possible? --- Miracles: their possibility and knowability --- Critical history and the supernatural --- Epistemology and the ethics of belief --- The incarnational narrative as historical: evidence for belief --- The incarnational narrative as historical: grounds for belief --- Putting the two stories together --- Historical scholarship and the layperson: a case study --- Conclusions: deeper encounters with historical scholarship and prospects for apologetics.
Includes bibliographical references (pages 356-367) and index.
Also available on the Internet to subscribing institutions.
Keywords: Jesus Christ -- Person and offices -- Biblical teaching; Jesus Christ -- Historicity; Bible. -- Criticism, interpretation, etc. -- History -- 20th century; Bible. -- Evidences, authority, etc; Incarnation -- Biblical teaching; Atonement -- Biblical teaching